Embodied Cognition in ‘1st appeal’: Integrating Spoken Word, Sound, And Movement as Choreographic Tools - Mohd Zahid, Muhammad Fairul Azreen; Abdul Rahman, Mohd Kipl; Salehuddin, Ahmad Kamal Basyah; Musa, Syahrul Fithri; Yanti Heriyawati (Harmonia: Journal of Arts Research and Education, 2025)
This research investigates the intersections of embodied cognition, language, and culture in dance, drawing on theoretical frameworks from anthropology and performance studies. Through an Auto Ethnomethodological approach, using the case study of “1st APPEAL” self-creation, this study examines how dancers employ spoken word, sound, and movement to interpret and negotiate choreographic intentions. By applying embodied cognition as a lens, this research reveals the complex relationships between language, culture, and embodiment in dance. This research lies in its innovative application of embodied cognition to dance practices, highlighting the crucial role of embodied experiences in shaping dancers’ understanding and execution of choreographic intentions. This research will contribute to a deeper understanding of the intricate relationships between language, culture, and embodiment in dance, providing valuable insights for dance practitioners, choreographers, and educators. The findings also underscore the importance of considering embodied and cultural contexts in dance practices, ultimately enriching our understanding of choreographic tools and creative processes.